A two-terminal perpendicular spin-transfer torque based artificial neuron. (20th September 2018) - Kondo, Kei; Choi, Jin-Young; Baek, Jong-Ung; Jun, Han-sol; Jung, Sunhwa; Shim, Tae-Hun; Park, Jea-Gun
Abstract: A two-terminal perpendicular spin-transfer torque (p-STT) based neuron with a 100  ×  100 nm device size was fabricated with a p-STT magnetic tunneling junction (MTJ) spin valve. It performed well in the integrate-and-fire event of the input voltage pulse (spike) cycles, which originate from the imperfect structure of the MgO tunneling barrier in a p-STT MTJ spin valve (i.e. a nano-scale poly-grain size distribution of the MgO tunneling barrier). In particular, the integrate-and-fire cycles rapidly increase as the input voltage pulse (spike) amplitude, width, and external assistant perpendicular magnetic field decrease.